Immune-related adverse events with immune checkpoint inhibitors: Special reference to the effects on the lungs. Issue 14 (9th April 2021) - Hirata, Aya; Saraya, Takeshi; Kobayashi, Fumi; Noda, Akinari; Aso, Kaori; Sakuma, Sho; Kurokawa, Nozomi; Inoue, Manami; Mikura, Sunao; Oda, Miku; Ishida, Manabu; Honda, Kojiro; et al.
Abstract : Abstract: Immune checkpoint inhibitors (ICIs) have emerged as evolutionary treatments for malignant diseases. Although ICIs can cause immune-related adverse events (irAEs) in various organs, precise timing after ICI initiation has been scarcely reported. Elucidating the effects of irAEs, such as time to onset, involvement of major organs, influence on progression-free survival (PFS), and overall survival (OS), are critical issues for physicians. Furthermore, lung-irAE as a whole is not well known. We conducted a retrospective study of 156 patients who were treated with ICIs and compared 82 irAE patients with 74 non-irAE patients. This study clearly demonstrated that the preferred period after induction of ICIs was significantly longer in lung-irAE than in other major organs (skin, digestive tract, and endocrine). The effect of irAEs on PFS and OS was evident PFS in the irAE group (n = 82) (median 128 days, interquartile range [IQR] 62–269 days, P = .002) was significantly longer than that in the non-irAE group (n = 74) (median 53 days, IQR 33–151 days). Similarly, OS was significantly longer in the irAE group (median 578 days, IQR 274–1027 days, P = .007) than in the non-irAE group (median 464 days, IQR: 209–842 days). However, this positive effect of irAEs in the lungs was not proportional to the extent of severity. Lung-irAEs can occur at a later phase than non-lung-irAEs and seemed not to prolong OS and PFS. However, further studies are needed to support these findings. Abstract : Supplemental Digital Content is available in the text